Low-pressure uniform plasma generator based on hollow cathode for ion plasma technologies - Khomich, V.A.; Ryabtsev, A.V.; Nazarenko, V.G. (Problems of Atomic Science and Technology, 2022)
The current paper describes the results of the improvement of a volumetric high-current low-pressure plasma generator. The device was made on the basis of a hollow cathode with a gas-magnetron ignition of the discharge and an auxiliary arc discharge for the cathode heating up to thermionic emission temperature. The device was operated at a working gas pressure of 0.1…1 Pa and had an electron concentration of 10¹⁰…5·10¹¹ cm⁻³. It was shown that the addition of the auxiliary electrode after the emission hole of the canoed unit lead to the improvement of generated plasma characteristics. This plasma generator may be used in the processes of ion-plasma technologies (oxidation, nitration in non-hydrogen media), as well as in energy-saving technologies of combined ion-plasma processing of structural materials.